St. Luke's missiology a cross-cultural challenge - Dollar, Harold E. (Pasadena, CA William Carey Library, 1996)
Includes bibliographical references and indexes.
Keywords: Bible. N.T. Luke -- criticism, interpretation, etc; Bible. N.T. Acts -- criticism, interpretation, etc; Missions -- history -- early church, ca. 30 - 600.; Sociology, biblical